Аксіологічна основа публіцистики Є. Сверстюка як спосіб формування ціннісної парадигми соціуму - Жванія, Людмила Вікторівна (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті розглядаються світоглядні константи публіциста, письменника-дисидента Євгена Сверстюка, визначальним серед яких постають концепти свобода, гідність, добро, істина. Зазначені світоглядні універсалії постають духовними орієнтирами в суспільному дискурсі, забезпечують морально-етичне та філософське підґрунтя для розбудови демократичного суспільства. У роботі доводиться теза про те що, світоглядна публіцистика Є. Сверстюка, актуалізуючи етичний потенціал християнської філософії, а також ідеалістичної філософії Канта, постає важливим чинником впливу на формування аксіологічної парадигми українського соціуму.

Eugene Sverstyuk was one of the most prominent figures of the era of the sixties, one of its creators and characters, so its world outlook, values, his work is largely an expression of the ideals of this cultural era. The article deals with the philosophical constants Eugene Sverstiuk – essayist, dissident writer. In our opinion the determinant in his worldview are the concepts of freedom, dignity, truth, goodness. These philosophical universals become spiritual reference points in the public, discourse ethical and philosophical basis for the development of a democratic society. The paper substantiates the idea that ideological journalism E. Sverstiuk, actualizing the ethical potential of Christian philosophy and idealist philosophy of Kant, it becomes an important factor of influence on the formation of axiological paradigm of Ukrainian society.
Axiological Principles Journalism Sverstyuk E. as a Way of Formation Values Paradigm of Society
Keywords: Сверстюк; свобода; гідність; добро; істина; цінності; Sverstyuk; value; freedom; dignity; good; truth